Metal–Organic Framework (MOF)‐Derived Nanoporous Carbon Materials. Issue 9 (10th April 2019) - Marpaung, Freddy; Kim, Minjun; Khan, Junayet Hossain; Konstantinov, Konstantin; Yamauchi, Yusuke; Hossain, Md. Shahriar A.; Na, Jongbeom; Kim, Jeonghun
Abstract: Metal–organic framework (MOF)‐derived nanoporous carbon materials have attracted significant interest due to their advantages of controllable porosity, good thermal/chemical stability, high electrical conductivity, catalytic activity, easy modification with other elements and materials, etc. Thus, MOF‐derived carbons have been used in numerous applications, such as environmental remediations, energy storage systems (i.e. batteries, supercapacitors), and catalysts. To date, many strategies have been developed to enhance the properties and performance of MOF‐derived carbons. Herein, we introduce and summarize recent important approaches for advanced MOF‐derived carbon structures with a focus on precursor control, heteroatom doping, shape/orientation control, and hybridization with other functional materials. Abstract : MOF‐derived carbon : The most recent important developments in metal–organic framework (MOF)‐derived carbon structures are summarized, with a focus on precursor control, heteroatom doping, shape/orientation control, and hybridization with other functional materials during synthesis.